Sea passages: cultural flows in Caribbean poetry. Issue 4 (1st October 2016) - Neumann, Birgit; Rupp, Jan
ABSTRACT: In Caribbean poetry, it is time and again the sea, as site of the Middle Passage and as a marker of island experiences, of displacement and belonging, which gives shape to an inherently polyvalent poetics of location. The sea pervades many Caribbean poems, both as a historical contact zone and as an imaginative principle of a new kind of nomadic and mobile epistemology. While the "Black Atlantic" paradigm fruitfully emphasizes transit and transcultural exchange, recent scholarship has also explored the sea as a site of dwelling and a more localized Caribbean place. Ecocritical readings in particular have highlighted the role of regional environments. Moreover, they have pinpointed a long-standing intellectual concern by which Caribbean writers have turned to land and sea as a way of reconstituting poetic traditions and historical narratives. Similarly, this article will discuss "sea passages" in a double, though always complementary, sense: passages across and to the sea, that is, precisely in order to accommodate the complex cultural flows to, fro and within the Caribbean, rather than reiterating spatial binaries which writing from and about the region frequently deconstructs itself. Taking current reappraisals of poetry and place in the Caribbean as a point of departure, the article will analyse a range of little discussed and more recent works in which the sea supplies poetic themes, fluid metaphors and symbolic forms that are in the process of becoming.